2009
DOI: 10.1152/ajpcell.00533.2008
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hypoxia attenuates VEGF signaling and angiogenic responses by downregulation of KDR in human endothelial cells

Abstract: Coronary artery disease results in progressive vascular stenosis associated with chronic myocardial ischemia. Vascular endothelial growth factor (VEGF) stimulates endothelial cell angiogenic responses to revascularize ischemic tissues; however, the effect of chronic hypoxia on the responsiveness of endothelial cells to VEGF remains unclear. We, therefore, investigated whether hypoxia alters VEGF-stimulated signaling and angiogenic responses in primary human coronary artery endothelial (HCAE) cells. Exposure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
53
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 55 publications
9
53
0
4
Order By: Relevance
“…21,22 A recent report indicated that chronic hypoxia attenuates VEGF signaling and angiogenic responses by downregulation of VEGF receptor 2 in human endothelial cells. 23 We confirmed that VEGF receptor 2 expression in the aging rat kidney was decreased compared with that in young rat kidney. This may provide a novel explanation for impaired angiogenic responses to VEGF in the aging kidney.…”
Section: Discussionsupporting
confidence: 73%
“…21,22 A recent report indicated that chronic hypoxia attenuates VEGF signaling and angiogenic responses by downregulation of VEGF receptor 2 in human endothelial cells. 23 We confirmed that VEGF receptor 2 expression in the aging rat kidney was decreased compared with that in young rat kidney. This may provide a novel explanation for impaired angiogenic responses to VEGF in the aging kidney.…”
Section: Discussionsupporting
confidence: 73%
“…Studies of VEGFR2 expression in animal models of brain ischemia and in vitro models of neuronal or brain tissue hypoxia have yielded conflicting results. In some, VEGFR2 was upregulated [69][70][71][72][73] and in others, decreased [74][75][76]. Other factors that may account for the reduced or unchanged microvessel density in hyperperfused cortex in AD [3] include sequestration of VEGF by Aβ42 [55], the decreased VEGFR1:sVEGFR1 ratio (see above), and binding of Aβ42 to VEGFR2 -shown by Patel et al [2010] to block VEGF-mediated signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Growth of these endothelial pillars leads to sinusoidal multiplication by successive fusion and partitioning of the existing vascular lumens [80]. A recent study with human endothelial cells shows that chronic hypoxia attenuates VEGF signaling and angiogenic responses by down-regulation of VEGFR-2 [81]. As stated above, most of HCCs originate from fibrosis and cirrhosis, which undergo chronic hypoxia and VEGFR-2 levels were down-regulated in both tumor and in adjacent tissue [78], preferring intussusceptive angiogenesis instead of sprouting angiogenesis.…”
Section: Intussusceptive Angiogenesis In Hccmentioning
confidence: 99%